Efektivitas Latihan Drill Lob dan Multishuttle terhadap Ketepatan Pukulan Lob Atlet Bulutangkis PB. Sahabat - Lalu Sapta Wijaya Kusuma; Jamaludin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to analyze the effectiveness of drill lob and multishuttle training methods on the lob shot accuracy of badminton athletes at PB. Sahabat. The research employed an experimental method with a two-group pretest-posttest design. The sample consisted of 20 athletes, divided into two training groups. Data were collected using a forehand overhead lob test, conducted ten times per participant. Data analysis using pairedsample t-test and independent sample t-test revealed that both training methods significantly improved lob shot accuracy, with p-values of 0.000 < 0.05. The drill lob group showed a 23.80% improvement, while the multishuttle group improved by 27.91%. Furthermore, the difference between the two groups was statistically significant (p = 0.003), with the multishuttle method yielding better results. These findings indicate that structured training approaches tailored to technical skill characteristics can significantly enhance athletic performance. This study recommends the multishuttle method as an effective approach for developing lob shot accuracy in youth badminton training.